Financial Literacy In Gen Z Generation (Case Study at Bina Taruna University Gorontalo) - Fitria Akibun; Henro Prayitno; Ria Z; Nur Otto (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2025)
This study aims to assess the level of financial literacy among Generation Z students at Bina Taruna Gorontalo University, focusing on personal financial management, the influence of social media on financial decisions, and the use of financial applications and tools. The research method employed is a quantitative approach with a descriptive design, involving data collection through surveys distributed to students. The findings reveal that the majority of students frequently create monthly budgets (42.9%) and have the habit of comparing prices before making purchases (71%), indicating a relatively good level of financial awareness. However, there is still a lack of saving habits, as more than half of the students do not have savings (52.4%). The influence of social media on students' financial decisions is quite significant, with 52.4% of students acknowledging its impact. The use of financial applications is also relatively low, with only 38% of students using them frequently. In conclusion, financial literacy among students at Bina Taruna Gorontalo University needs to be improved, particularly in the areas of saving and utilizing financial applications. An intensive financial education program is required to better equip students with the skills to manage their personal finances wisely.